Implementation of the Business Model Canvas (BMC) and Projection of Financial Analysis as a Solution for the Continuity of Home Industry Activities - Ni Komang Mela Tri Utari (Magister Manajemen, Program Pascasarjana, Universitas Warmadewa, 2023)
In the midst of very tight similar business competition, a business is expected to be able to meet market desires. When opening a new business, of course, an entrepreneur needs careful calculations and proper market analysis. This study aims to analyze the implementation of the Business Model Canvas (BMC) and projection of financial analysis as a solution for the continuity of home industry activities. The method used in analyzing the data is the Internal Rate of Return (IRR) and Net Present Value (NPV). The result of this study showed that with the Business Model Canvas (BMC) analysis, Freshy Salad Bali can find out how a business model in developing strategies in achieving company goals. There are 9 elements of the Business Model Canvas described below. The business feasibility proposal based on the projected financial analysis in this study obtained positive NPV results of Rp. 91,505,796 and a value and IRR greater than WACC, namely with a value of 64% which can be concluded that the Freshy Salad Bali business is feasible to run. The company hopes that this